Giovanni Alfonso Borelli: The Precursor of Medial Pivot Concept in Knee Biomechanics - Piolanti, Nicola; Polloni, Simone; Bonicoli, Enrico; Giuntoli, Michele; Scaglione, Michelangelo; Indelli, Pier Francesco (Joints, 2018)
A new philosophy of science and medicine had spread throughout the 17th-century Italy: the “Scientific Revolution.” Giovanni Alfonso Borelli (1608–1679) was one of the most charismatic and brilliant scientists of his generation in Europe. He extended to biology the rigorous analytic methods developed by his indirect mentor Galileo in the field of mechanics. In his masterpiece “De Motu Animalium,” Borelli analyzed structure, motion, balance, and forces concerning almost all the principal joints of the human body, in static and dynamic situations. In particular, he accurately studied the anatomy and biomechanics of the knee joint. He sustained that femoral condyles shift backward during flexion, allowing a wider range of movement. Furthermore, he observed that, when the knee flexes, the lateral condyle moves backward more than the medial condyle: this concept is nowadays known as medial pivoting. The aim of this article is to describe the life and work of this important Italian scientist and to present his unrecognized contribution to modern knee biomechanics.
Keywords: knee biomechanics; femoral rollback; medial pivot; total knee arthroplasty; Giovanni Alfonso Borelli